دعم المشتقات النفطية في سورية واقع وأفاق (حالة دراسية-مصفاة بانياس) - محمود, يوسف; عروس, محمد; إسماعيل, عدنان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث واقع دعم المشتقات النفطية في سورية, حيث يحاول إلقاء الضوء على هذه العملية من خلال التعريف بداية بتكاليف المشتقات النفطية المنتجة في شركة مصفاة بانياس، ومقدار الدعم لكل منها، وريعيتها، ثم ينتقل البحث للخوض في مشكلات دعم المشتقات النفطية التي برزت في السنوات الأخيرة، لاسيما تهريبه إلى البلدان المجاورة في ظل المستويات الجنونية التي وصلتها أسعار النفط الخام، كما يحاول البحث الربط بين عملية دعم المشتقات النفطية والموازنة العامة للدولة، من خلال عدة نواحي أبرزها: انخفاض إنتاج النفط الخام السوري، والارتفاع الكبير لأسعاره الذي يغطي هذا الانخفاض حاليا. إضافة إلى ارتفاع استهلاك المازوت الذي كبد الحكومة السورية في العامين المنصرمين خسائر فادحة، وفي النهاية يحاول البحث تقديم عدة حلول لهذه المشكلة: كتنظيم عملية الدعم وتحديد المستفيدين منها، وإعادة هيكلة قطاع الصناعة النفطية بشكل يعوض عن انخفاض عائدات النفط الخام. This study deals with the actual subsidy of petroleum derivatives in Syria. It casts light on this process by introducing the costs of the petroleum derivatives produced at BRC. It also shows the amount of subsidy for each and its returns. This paper examines the problems which appeared last year to do with the subsidy of petroleum derivatives, especially smuggling them into neighboring countries, given the huge levels of increase in crude oil prices. This study also tries to link the subsidy of petroleum derivatives to the country's budget, taking the following into consideration: A decrease of Syrian crude oil production and the huge increase of its prices offsetting the present decrease, and an increase of fuel oil consumption has meant the Syrian government incurring huge losses over the last two years. Finally, this paper also tries to provide solutions to this problem by way of regulating the subsidy process and identifying beneficiaries, and of re-structuring the petroleum industry sector in order to compensate the decrease of crude oil returns.